The Effect Of Telemedicine And Brand Awareness On The Decision To Treatment And Its Impact On Return Visits Of Outpatient Hospital Patients X - Fransiskus Agus Priono; Maura Linda Sitanggang; Derriawan Derriawan (Jurnal Info Sains : Informatika dan Sains, 2023)
The pandemic situation has not only caused changes in health management, but has also caused business competition in the pharmaceutical sector. The development of information technology is utilized in pharmaceutical services such as telemedicine. Hospital X is one of the hospitals that has implemented telemedicine services since 2020. The implementation of telemedicine services is one of the ways Hospital X has responded to the impact of the pandemic and developments in information technology. This service has been implemented since 2020 along with the pandemic which has changed the format of services in many health facilities, including hospitals. Technological developments also make hospital customers have high expectations for health services. Research Objectives: This study aims to determine the effect of telemedicine and Brand Awareness on treatment decisions and impact on patient repeat visits at X Hospital. Research Methodology: The authors used a cross-sectional study design with quantitative methods, measuring telemedicine service variables, brand awareness, treatment decisions, and patient repeat visits with a sample size of 150. Results: The telemedicine service variable has a mean value of 3.99. The brand awareness variable has a mean value of 4.09. medication decision variable has a mean value of 4.32. the patient return visit variable has a mean value of 4.11. Conclusion: There is an influence of telemedicine services on treatment decisions while there is no influence of telemedicine services and brand awareness on treatment decisions. Brand Awareness also influences Patient Return Visits. However, telemedicine has no effect on patient repeat visits. Treatment Decisions Affect the patient's repeat visit.